VD_FINDINFO Jug / 2022 / 384 vom 9. Mai 2022 - VD Tribunal cantonal (2022)
LOI FÉDÉRALE CONTRE LA CONCURRENCE DÉLOYALE, CHAUFFEUR, TAXI | 2 LCD, 23 LCD, 3 al. 1 let. b LCD, 3 al. 1 let. d LCD, 126 CPP (CH)